Linear Active Disturbance Rejection Control for Lever-Type Electric Erection System Based on Approximate Model. (27th March 2019) - Niu, Hailong; Gao, Qinhe; Tang, Shengjin; Guan, Wenliang
Abstract : Linear active disturbance rejection control (LADRC) algorithm is proposed to realize accurate trajectory tracking for the lever-type electric erection system. By means of system identification and curve fitting, the approximate model is built, which is consisting of the servo drive system with velocity closed-loop and the lever-type erection mechanism. The proportional control law with velocity feedforward is designed to improve the trajectory tracking performance. The experimental results verify that, based on approximate model, LADRC has better tracking accuracy and stronger robustness to the disturbance caused by the change of intrinsic parameters compared with PI controller.